J-aggregation induced emission enhancement of BODIPY dyes via H-bonding directed supramolecular polymerization: the importance of substituents at boron. Issue 15 (27th May 2021) - Zhang, Yongjie; Yuan, Siyuan; Liu, Ping; Jing, Lei; Pan, Hongfei; Ren, Xiang-Kui; Chen, Zhijian
Abstract : For uracil-functionalized BODIPY dyes 1a–c, AIEE upon H-bonding directed J-aggregation was observed for the two dyes bearing alkyne groups at boron while the BF2 -chelated dye displayed ACQ, indicating the crucial role of the substituents at boron. Abstract : Two new boron-dipyrromethene (BODIPY) dyes 1b and 1c, bearing two uracil units at the 2, 6-positions and solubilizing alkyne groups at boron atoms, were synthesized and characterized. The UV/Vis absorption and fluorescence spectroscopic studies indicated that in nonpolar solvents these BODIPY dyes supramolecularly polymerized into J-aggregates, which exhibited outstanding optical properties, such as narrowed absorption and emission bands with reduced fluorescence lifetime and increased quantum yields with respect to that for monomers. The mechanism of the polymerization of 1b and 1c was analysed by temperature- and concentration-dependent spectroscopy and studied with a nucleation–elongation model. Measurements of concentration-dependent 1 H NMR and AFM demonstrated the H-bonding directed self-assembly of J-aggregates of dyes 1b and 1c, which led to the formation of one-dimensional nanowires of these dyes. Further molecular modelling studies and calculations based on exciton theory indicated that the bulky alkyne substituents at boron atoms effectively hindered the close contact between the π-faces of BODIPY chromophores, implying that the appropriate segregation of supramolecular polymer chains could be crucial for the aggregation-induced emission enhancement (AIEE) for this class of BODIPY dyes, as compared with the fluorescence quenching observed for the J-aggregates of BODIPY 1a bearing F atoms at boron in our previous report.